Rehabilitation system for paraplegic patients using mind machine interface; a conceptual framework - Sherwani, Fahad; KSM Kader Ibrahim, Babul Salam; Huq, M. Saiful; Ahmad, Mohd Khairul Ikhwan; Nasir, N.H.M.; Rahman, K.A.A. (Asian Research Publishing Network (ARPN), 2015)
Mind-Machine Interface (MMI) is a newly surfaced term in the field of control engineering and rehabilitation systems. This technique, coupled with the existing functional electrical stimulation (FES) systems, can be very beneficial for effective rehabilitation of disabled patients. This paper presents a conceptual framework for the development of MMI based FES systems for therapeutic aid and function restoration in spinal cord injured (SCI) paraplegic patients. It is intended to acquire thought modulated signals from human brain and then use these signals to command and control FES as desired by the patient. The proposed setup can significantly assist the rehabilitation and recovery of paraplegic patients due to the ease of control for the user.